Morphological and Molecular characterization of rhizoctonia oryzae sativae in Bangladesh - Jahan, SB; Ali, MA; Alam, MS; Moni, ZR; Latif, MA (SAARC Journal of Agriculture, 2019)
Aggregate sheath spot disease of rice caused by Rhizoctonia oryzaesativae has emerged in higher incidence in North-Western region of Bangladesh. Thirty isolates of R. oryzae-sativae were studied by using morphological and molecular marker. Isolates were confirmed using specific primer where a single band of 1200bp was amplified. Two distinct groups relatively slow and faster were found in mycelal growth. Molecular characterization was done using four primers and DNA band ranged from 0.25 to 2.21 kb. A combined dendrogram was constructed which separated the isolates into three groups at 69.6% similarity level. All isolates placed in two major clusters except isolate RA-1 placed in cluster group III but were not grouped according to their geographic origins. Fast growing isolates have been placed in Group II while slow growing isolates in cluster group I. The similarity coefficient values of the dendrogram profile ranged from 0.36 to 0.98 with an average of 0.67. Diversity of different isolate showed that significant variation was present among the isolate and were not genetically identical. SAARC J. Agri., 16(2): 119-128 (2018)